(untitled) (Champaign, Ill., 2004)
The book offers comprehensive overview chapters on vitamin A, retinoids, and carotenoids, including different aspects of their uptak, molecular structure, transport, storage, metabolism, transcriptional asctivity, and roles in human health. There is also a thorough review of the special role that vitamin A intake plays in the health status of developing countries.
Keywords: Carotenoids,Carotenoids,Retinoids,Retinoids; Health aspects,Molecular aspects,Health aspects,Molecular aspects